PENGARUH KEAHLIAN AKUNTANSI DAN KEUANGAN KOMITE AUDIT DAN DEWAN KOMISARIS TERHADAP MANAJEMEN LABA - Dwiharyadi, Anda (Jurnal Akuntansi dan Keuangan Indonesia, 2017)
This study examines whether the proportion of members of the audit committee and board of commissioner with accounting and/or financial expertise reduces earnings management. Accounting expertise is separated to financial expertise because accounting expertise is assumed to be able to cope with more earnings management while financial expertise focuses more on the financial management of company’s operations. By using panel data, this study finds that the existence of members of audit committee and board of commissioner with accounting expertise or financial expertise do not have a negative effect on earnings management. However, the existence of both expertises on members of board of commissioner reduces earnings management, while that is not the case for audit committee.